Lithium chloride with immunomodulatory function for regulating titanium nanoparticle-stimulated inflammatory response and accelerating osteogenesis through suppression of MAPK signaling pathway - Yang C (Dove Medical Press, 2019)
Chao Yang,* Wei Wang,* Kechao Zhu, Wei Liu, Yao Luo, Xiangwei Yuan, Jiaxing Wang, Tao Cheng, Xianlong Zhang Department of Orthopedics, Shanghai Jiao Tong University Affiliated Sixth People’s Hospital, Shanghai 200233, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xianlong Zhang; Tao ChengDepartment of Orthopedics, Shanghai Jiao Tong University Affiliated Sixth People’s Hospital, Shanghai 200233, People’s Republic of ChinaTel +86 216 436 9183Fax +86 216 470 1363Email dr_zhangxianlong@163.com; dr_tao.cheng@hotmail.comBackground: Wear particle-induced inflammatory osteolysis and the consequent aseptic loosening constitute the leading reasons for prosthesis failure and revision surgery. Several studies have demonstrated that the macrophage polarization state and immune response play critical roles in periprosthetic osteolysis and tissue repair, but the immunomodulatory role of lithium chloride (LiCl), which has a protective effect on wear particle-induced osteolysis by suppressing osteoclasts and attenuating inflammatory responses, has never been investigated.Methods: In this work, the immunomodulatory capability of LiCl on titanium (Ti) nanoparticle-stimulated transformation of macrophage phenotypes and the subsequent effect on osteogenic differentiation were investigated. We first speculated that LiCl attenuated Ti nanoparticle-stimulated inflammation responses by driving macrophage polarization and generating an immune micro-environment to improve osteogenesis. Furthermore, a metal nanoparticle-stimulated murine air pouch inflammatory model was applied to confirm this protective effect in vivo.Results: The results revealed that metal nanoparticles significantly activate M1 phenotype (proinflammatory macrophage) expression and increase proinflammatory cytokines secretions in vitro and in vivo, whereas LiCl drives macrophages to the M2 phenotype (anti-inflammatory macrophage) and increases the release of anti-inflammatory and bone-related cytokines. This improved the osteogenic differentiation capability of rat bone marrow mesenchymal stem cells (rBMSCs). In addition, we also provided evidence that LiCl inhibits the phosphorylation of the p38 mitogen-activated protein kinase (p38) and extracellular signal-regulated kinase (ERK) pathways in wear particle-treated macrophages.Conclusion: LiCl has the immunomodulatory effects to alleviate Ti nanoparticle-mediated inflammatory reactions and enhance the osteogenic differentiation of rBMSCs by driving macrophage polarization. Thus, LiCl may be an effective therapeutic alternative for preventing and treating wear debris-induced inflammatory osteolysis.Keywords: lithium chloride, Ti nanoparticle, macrophage polarization, osteoimmunology, osteogenesis, immunomodulatory